The 'Urban Age' in Question. (4th December 2013) - Brenner, Neil; Schmid, Christian
Abstract Foreboding declarations about contemporary urban trends pervade early twenty‐first century academic, political and journalistic discourse. Among the most widely recited is the claim that we now live in an 'urban age' because, for the first time in human history, more than half the world's population today purportedly lives within cities. Across otherwise diverse discursive, ideological and locational contexts, the urban age thesis has become a form of doxic common sense around which questions regarding the contemporary global urban condition are framed. This article argues that, despite its long history and its increasingly widespread influence, the urban age thesis is a flawed basis on which to conceptualize world urbanization patterns: it is empirically untenable (a statistical artifact) and theoretically incoherent (a chaotic conception). This critique is framed against the background of postwar attempts to measure the world's urban population, the main methodological and theoretical conundrums of which remain fundamentally unresolved in early twenty‐first century urban age discourse. The article concludes by outlining a series of methodological perspectives for an alternative understanding of the contemporary global urban condition.